How to change students' images of science and technology - Scherz, Zahava; Oren, Miri (Science education (Salem, Mass.), 2006)
This paper examines the images middle school students have of science and technology, the workplaces, and the relevant professions. It also describes the effect on these images caused by an instructional initiative, “Investigation into Science and Technology” (IST), designed to introduce students to science and technology in the “real life.” Students' images were delineated via questionnaires, drawing tasks, and interviews before and after their participation in the IST program. The sample consisted of ∼100 students from six classes (eighth or ninth grade) of three schools. We found that before the IST intervention students' images about the scientific or technological environments were superficial, unreal, and even incorrect. Their impressions of the characteristics of scientists and technologists were superficial, misleading, and sometimes reflected ignorance. The findings demonstrate that the IST program stimulated a positive effect on students' images. Their preconceptions were altered in several dimensions: in “the cognitive dimension,” from superficial and vague to precise and correct images; in “the perceptive dimension,” from stereotypic to rational and open‐minded images; and in “the affective dimension,” from negative to positive attitudes. © 2006 Wiley Periodicals, Inc. Sci Ed 90:965–985, 2006